Pallidal activity recorded in patients with implanted electrodes predictively correlates with eventual performance in a timing task. - Brown, P; Williams, D; Aziz, T; Mazzone, P; Oliviero, A; Insola, A; Tonali, P; Di Lazzaro, V (2002)
Here we seek to establish whether there are activities in the human pallidum that may predict a specific aspect of performance, timing. When recording from two patients with Parkinson's disease and primary generalised dystonia following functional neurosurgery we found that the amplitude of oscillatory pallidal activity occurring prior to the completion of a bimanual timing task was strongly correlated with eventual task duration. The frequency of this oscillatory activity was around 25 Hz. We conclude that the human pallidum may be involved in the prediction of movement timings and that such internal estimates may be reflected in amplitude modulation of oscillatory activity around 25 Hz.